A common random fixed point theorem and Application to Random Integral Equations - Rashwan, Rashwan Ahmed; Albaqeri, D. M. (International Journal of Applied Mathematical Research, 2014)
The aim of this paper is to prove a fixed point theorem of a contraction mappings of a pair of weakly increasing mappings using an altering function in a partially ordered complete separable metric spaces. Our theorem is useful to determine a large of nonlinear problems. We discuss the existence of a common solution to a system of nonlinear random integral equations. Keywords: Common random fixed point, Nonlinear integral random equation, Partially ordered metric spaces, Random variable, Weakly increasing.